Strategi Kepala Madrasah Dalam Membangun Brand Image Madrasah - Anis Salamah; Moh Syamsul Falah (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2024)
This research focuses on the madrasa head's strategy in building an image of the madrasa. Brand Image is a set of assumptions that exist in the minds of consumers about a brand which is formed from various sources. In building a brand image, a strategy is needed. Strategy is a method used to mobilize all the capabilities of all the resources available in the organization so that they can work together to achieve the goals that have been set. This research uses a descriptive qualitative method involving data collection techniques in the form of in-depth interviews, observation, and document analysis. The results of this research are: 1. There are stages in determining a madrasa head's strategy: (a) Formulate a strategy before it is determined so that it is easy to analyze strengths and opportunities. (b) Invite all members to be involved in implementing the agreed strategy, and the creativity of madrasah heads continues to develop. (c) Evaluation of the implementation and implementation of strategies that have been carried out together. 2. Brand images that are being built are Images of adiwiyata, sports madrasas, Islamic boarding school-based madrasas, and arts madrasas. 3. Strategy for madrasa heads to build brand image: (a) Increase accreditation. (b) Improving educator performance. (c) Increasing student achievement. (d) Improving programs in madrasas 4. Factors forming perceptions of educational institutions: cultural background, past experiences, and developing news